PERLINDUNGAN HUKUM MEREK TERKENAL (KASUS SENGKETA MEREK PIERRE CARDIN PERANCIS VS INDONESIA) - Kennedy Wijaya; Jeane Neltje (Faculty of Law - Tarumanagara University, 2020)
The tendency of brands that have sprung up in Indonesia has given rise to unhealthy competition so violations have often sprung up. The problem faced is how to resolve dispute cases in Central Jakarta Commercial Court Decision No.15 / PDT.SUS / MEREK / 2015 Jo Cassation Decision No.557K / PDT.SUS-HKI / 2015 regarding the famous brand pierre cardin based on uu brand and legal protection against the owner of the famous brand Pierre Cardin of France for the registration of the Indonesian pierre cardin trademark received by the Directorate General of IPR. The research method used in this paper is a normative legal research method. Normative legal methods are research methods that use literature to discuss existing legal issues. Result research show that Central Jakarta Commercial Court Decision Number 15 / PDT.SUS/MEREK/ 2015 Jo Cassation Decision Number 557K / PDT.SUS-HKI / 2015 and Decision Number 49PK / Pdt.Sus-HKI / 2018 related to Pierre Cardin's trademark dispute not in accordance with the laws and regulations especially the Trademark Law protection of trademarks is specifically regulated in Articles 68 and 76 Paragraph (1) of the old Trademark Law and Articles 76 and 83 Paragraph (1) of the New Trademark Law. This article facilitates trademark owners if a violation occurs against their trademark, the trademark owner can file a lawsuit to the Commercial Court or with an alternative dispute resolution. Regarding the decision, the judge has not obeyed the norms governing the mark and the judge has violated the trademark rules.